Transformasi Pembelajaran Bahasa Indonesia di Sekolah Dasar Berbasis Literasi Abad 21 dan Teknologi Digital - Haerummi Haerummi; Erna Wati; Indana Zulpa (PGSD UNU NTB, 2025)
This study aims to explore the transformation of Indonesian language learning in elementary schools through the integration of 21st-century literacy and digital technology. The study emphasizes the comprehensive development of literacy skills, including reading, writing, critical thinking, creativity, collaboration, and communication within a technology-based learning context. A descriptive qualitative method was employed, with data collected through observations, interviews, and analysis of digital learning documents. The sample consisted of fifth- and sixth-grade students from several elementary schools that implement interactive digital media, gamification, and digital storytelling. The results indicate that the integration of digital technology significantly enhances student engagement, learning motivation, and literacy competence. Students become more active in composing texts, understanding language concepts, and applying critical and creative thinking skills. Collaborative activities and technology-based projects strengthen communication, teamwork, and the ability to evaluate peers’ work. Supporting factors include teacher motivation, student readiness, and the availability of digital resources. Challenges such as disparities in digital skills and limited infrastructure can be addressed through teacher training and appropriate pedagogical strategies, leading to more effective, interactive, and sustainable learning.